Study of phase transitions in α-Fe2O3 during mechanical grinding in a high-energy ball mill - Elkin, V. D.; Lysenko, E. N.; Vlasov, V. A.; Surzhikov, A. P.; Knyazev, Yu. V. (Russian physics journal, 2025)
The phase transformations, taking place in α−Fe 2 O 3 during its mechanical grinding in an AGO-2C planetary ball mill with an aim to manufacture a Fe 3 O 4 -based magnetic powder, are studied. The grinding is performed using steel vials and balls under different modes, grinding times (up to 120 min), mill rotation frequencies (1290, 1820, 2220 rpm), processing media (water, isopropyl alcohol, dry grinding in air), degree of filling vials with balls and powder (from 1/12 to 2/3 of vial volume), and ball-to-powder mass ratios (from 2.5:1 to 20:1). It is shown that different grinding modes strongly affect the−Fe 2 O 3 →Fe 3 O 4 phase transition, resulting in different phase concentration ratios in the milled powder. It is noted that the magnetite concentration increases with the grinding energy density, which depends on the rotation frequency and grinding time. The most effective modes of the Fe 3 O 4 -based nanostructured powder manufacture are established, which involve the maximum rotation frequency, the grinding time up to 120 min, and the ball-to-powder ratio 10:1. The magnetic powder thus produced has the Curie temperature of 556 °C and the saturation magnetization of 65 emu/g.